2005
DOI: 10.1021/ol050203y
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Catalyzed Synthesis of 1,3-Dioxan-4-ylidenes

Abstract: [reaction: see text] A phosphine-catalyzed reaction of an allenoate with aldehydes furnished (2,6-diaryl-[1,3]dioxan-4-ylidene)-acetates 4 in excellent to moderate yields with complete diastereoselectivity and high E/Z-selectivities. Upon removal of the acetal functionality in this domino reaction product 4, delta-hydroxy-beta-ketoester 11 was obtained. The reported vinylphosphonium-based approach provides a new way to achieve a synthesis of delta-hydroxy-beta-ketoesters that differs from the classical dianion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(63 citation statements)
references
References 14 publications
3
58
0
2
Order By: Relevance
“…[138] Interestingly, Kwon and co-workers showed that the phosphane-catalyzed reaction of allenoates and aldehydes does not give the expected formal [3+2] cycloaddition products, 2,5-dihydrofurans. Depending on the catalyst struc-ture and reaction conditions, 1,3-dioxan-4-ylidenes 91 [139] or 2-pyrones 92 [140] can be prepared with high selectivity (Scheme 32). This change in the reaction pathway is traced to the fate of the intermediate zwitterion XL.…”
Section: Phosphane-catalyzed Cycloadditionsmentioning
confidence: 99%
“…[138] Interestingly, Kwon and co-workers showed that the phosphane-catalyzed reaction of allenoates and aldehydes does not give the expected formal [3+2] cycloaddition products, 2,5-dihydrofurans. Depending on the catalyst struc-ture and reaction conditions, 1,3-dioxan-4-ylidenes 91 [139] or 2-pyrones 92 [140] can be prepared with high selectivity (Scheme 32). This change in the reaction pathway is traced to the fate of the intermediate zwitterion XL.…”
Section: Phosphane-catalyzed Cycloadditionsmentioning
confidence: 99%
“…[136] Das Verfahren wurde erfolgreich in den Totalsynthesen von Hirsuten [137] und Hinesol genutzt. [138] Interessanterweise erhielten Kwon und Mitarbeiter bei der phosphankatalysierten Reaktion von Allenoaten mit Aldehyden nicht die erwarteten 2,5-Dihydrofurane als die formalen [3+2]-Cycloadditionsprodukte, sondern es entstanden -je nach Katalysatorstruktur und Reaktionsbedingungenhoch selektiv die 1,3-Dioxan-4-ylidene 91 [139] oder die 2-Pyrone 92 [140] (Schema 32). Diese Abweichung wird auf das intermediäre Zwitterion XL zurückgeführt.…”
Section: Phosphankatalysierte Cycloadditionenunclassified
“…Accordingly, a nitrogen-containing Lewis base such as triethylamine (Et 3 N) was also tried, but no reaction occurred under the same conditions (entry 6). Using PBu 3 (50 mol%) as the optimized catalyst, the solvent effects were then explored (entries 1,2,[7][8][9][10][11], all the reactions were carried out below the reflux temperature of the solvent. Compared with THF, toluene, CH 3 CN, DMF, DCM, and CCl 4 , CHCl 3 was the best reaction solvent in which the product 3a was obtained in 66% yield (entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…[5] This motif is also an important structural skeleton found in many natural products and bioactive molecules. [6] Alternatively, allenes could also react with aldehydes to produce dioxanes, pyrones, dihydropyrone, 1,3-dienes, or vinylcyclopropanes, and with ketones to construct dihydrofurans, [7] but there is only one example of galkyl allenates with aryl aldehydes giving tetrahydrofurans, in which the g-methyl or methylene was directly involved in the carbon-carbon bond-forming steps, [7g] rather than the normal [3+2] cycloaddition.…”
Section: Introductionmentioning
confidence: 99%